2009
DOI: 10.1097/ta.0b013e318182f77f
|View full text |Cite
|
Sign up to set email alerts
|

When Violence Strikes The Head, Neck, and Face

Abstract: HNF injuries are characteristic among victims of violence, although significant differences exist in the type of injuries, the location, and the trauma mechanism between men and women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
50
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 19 publications
14
50
0
3
Order By: Relevance
“…The significance of facial injuries in assault is well-established in younger assault victims, with 62%-83% of victims presenting to the Emergency Department having facial injuries. 34, 35, 42 The face is a common site of injury, likely because it is exposed and vulnerable to an assailant. 33, 34, 43 In addition, when desiring to incapacitate, badly hurt, or humiliate a victim, the head and face are attractive targets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significance of facial injuries in assault is well-established in younger assault victims, with 62%-83% of victims presenting to the Emergency Department having facial injuries. 34, 35, 42 The face is a common site of injury, likely because it is exposed and vulnerable to an assailant. 33, 34, 43 In addition, when desiring to incapacitate, badly hurt, or humiliate a victim, the head and face are attractive targets.…”
Section: Discussionmentioning
confidence: 99%
“…33, 34, 43 In addition, when desiring to incapacitate, badly hurt, or humiliate a victim, the head and face are attractive targets. 33, 43 Researchers have suggested that these injuries may be used to identify victims of violence or raise suspicion of violence-related injury 42, 4447 and have even begun to identify patterns among maxillofacial injuries that may be suggestive of assault rather than accident. 48 In a multi-center study, most common facial fractures after assault were of the mandible, zygoma, and orbit, with these prominent areas more likely injured given that a fist to the face is the most common mechanism of injury.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the clustering of head, face and neck injuries in young adult women appears to reflect physical violence between partners who are in IT or MVC relationships (Muelleman et al ., ; Novak, ; Johnson, ; Lau et al ., ; Brink, ) but not exclusively so, and this result raises issues for how middle‐aged and older people, both past and present, are recognised as victims of DV rather than assault or elder abuse. These problems are recognised more widely, as there are a growing number of dissenting voices in the clinical, forensic and social science literature who are concerned about the overreliance on models and ‘check‐lists’ of injury patterning (Engle Merry, ; Juarez & Hughes, ; Katerndahl et al ., ; Reijnders & Ceelen, ).…”
Section: Discussionmentioning
confidence: 99%
“…Child abuse is especially problematic as most children survive abusive injuries or the ensuing death is not detectible from the skeletal remains, although cases for abuse have been proposed by Blondiaux et al (2002) in France and by Wheeler et al (2007) in Egypt. If we look to clinical research for guidance, clinicians have been unsuccessful in their quest for skeletal abuse indicators among adults, although soft tissue facial injuries are profuse (Allen et al 2007;Brink 2009). We tend to assume that domestic violence was perpetrated by males, when in fact cultural anthropologists observe that active female participation is widespread particularly in same-sex relationships (McClennen 2005) or in polygynous societies, where altercations among co-wives are regarded as unimportant "nonevents" (Burbank 1994).…”
Section: Social and Cultural Meaningmentioning
confidence: 99%